Feasibility Study for the Transportation of Steel Billets by Amphibious Vehicle - Antikian, John L. (My University, 1975)
The problem of transporting steel billets from the No. 3 Bloom and Billet Mill to the No. 2 Rob Mill of The Steel Company of Canada is dealt with in this report. An original solution is proposed in the form of amphibious vehicles playing a water route in Hamilton Bay between the two mills.
The following Study will prove the feasibility of such a scheme.
Keywords: Mechanical Engineering; Mechanical Engineering